DNAH11 and a Novel Genetic Variant Associated with Situs Inversus: A Case Report and Review of the Literature - Fatemeh Sodeifian; Noosha Samieefar; Sepideh Shahkarami; Elham Rayzan; Simin Seyedpour; Meino Rohlfs; Christoph Klein; Delara Babaie; Nima Rezaei (Case Reports in Medicine)
Background. Primary ciliary dyskinesia (PCD), also known as the immotile-cilia syndrome, is a clinically and genetically heterogeneous syndrome. Improper function of the cilia causes impaired mucociliary clearance. Neonatal respiratory distress, rhinosinusitis, recurrent chest infections, wet cough, and otitis media are respiratory presentations of this disease. It could also manifest as infertility in males as well as laterality defects in both sexes, such as situs abnormalities (Kartagener syndrome). During the past decade, numerous pathogenic variants in 40 genes have been identified as the causatives of primary ciliary dyskinesia. DNAH11 (dynein axonemal heavy chain 11) is a gene that is responsible for the production of cilia’s protein and encodes the outer dynein arm. Dynein heavy chains are motor proteins of the outer dynein arms and play an essential role in ciliary motility. Case Presentation. A 3-year-old boy, the offspring of consanguineous parents, was referred to the pediatric clinical immunology outpatient department with a history of recurrent respiratory tract infections and periodic fever. Furthermore, on medical examination, situs inversus was recognized. His lab results revealed elevated levels of erythrocyte sedimentation rate (ESR) and C reactive protein (CRP). Serum IgG, IgM, and IgA levels were normal, while IgE levels were elevated. Whole exome sequencing (WES) was performed for the patient. WES demonstrated a novel homozygous nonsense variant in DNAH11 (c.5247G > A; p. Trp1749Ter). Conclusion. We reported a novel homozygous nonsense variant in DNAH11 in a 3-year-old boy with primary ciliary dyskinesia. Biallelic pathogenic variants in one of the many coding genes involved in the process of ciliogenesis lead to PCD.